Love without link? On sexuality and love in Lima - Ochoa Valdez, Piero (2019)
The article discusses the social forms which sexuality and love are experienced in Lima, in dialogues with the specialized literature, especially with the last work’s peruvian sociologist Pedro Pablo Ccopa (2011). New interpretations are presented -from a sociological view- on the phenomena of sex in hostels and hotels; and about reggaeton/’perreo’ as modern dance and sexual simulation. The author concludes that: i) it’s necessary to adequate delimitations about studied society in order to better understand the phenomenon as well as a possible generalization; ii) the new social forms without commitment —‘choque y fuga’, perreo, ‘friends with rights’, remember— are basically sexual forms, not love forms; iii) so, sexual forms do not critic the idea of love in contemporary world (romantic love); iv) it’s not a liberalization of Eros, instead, it’s an agony.